Blood metabolomic profile in patients with type 2 diabetes mellitus with diabetic peripheral neuropathic pain - Hung‐Chou Kuo; Chia‐Ni Lin; Sung‐Sheng Tsai; Chiung‐Mei Chen; Rong‐Kuo Lyu; Chun‐Che Chu; Long‐Sun Ro; Ming‐Feng Liao; Hong‐Shiu Chang; Yi‐Ching Weng; Jawl‐Shan Hwang (Journal of Diabetes Investigation)
ABSTRACT Aims This study aimed to identify metabolic markers for diabetic peripheral neuropathic pain (DPNP) in patients with type 2 diabetes mellitus (T2DM). Materials and Methods Blood metabolite levels in the amino acid, biogenic amine, sphingomyelin, phosphatidylcholine (PC), carnitines, and hexose classes were analyzed in nondiabetic control (n = 27), T2DM without DPNP (n = 58), and T2DM with DPNP (n = 29) using liquid chromatography tandem mass spectrometry. Variable importance projection (VIP) evaluation by partial least squares discriminant analysis was performed on clinical parameters and metabolites. Results Sixteen variables with VIP > 1.0 (P < 0.05) were identified across all patient groups, and 5 variables were identified to discriminate between the two T2DM groups. DPNP patients showed elevated fasting blood glucose, glutamate, PC aa C36:1, lysoPC a C18:1, and lysoPC a C18:2, while low‐density lipoprotein cholesterol, phenylalanine, and tryptophan were reduced. Glutamate, lysoPC a C18:1, and lysoPC a C18:2 discriminated T2DM with DPNP from those without DPNP with an AUC of 0.671. The AUC was improved to 0.765 when ratios of metabolite pairs were considered. Interpretation Blood metabolites include glutamate, and phospholipid‐related metabolites implicated in neuropathic pain may have the potential as biomarkers for DPNP. Further investigation is required to understand the mechanism of action of these altered metabolites in DPNP.